Tomasz Jarmużek, On the Sea-Battle Tomorrow That May Not Happen. A Logical and Philosophical Analysis of the Master Argument (Berno: Peter Lang, 2019), ss. 262 - Rzeczkowska, Anna (Ruch Filozoficzny, 2021)
-